X-RAY STANDING WAVE STUDIES OF MINERALS AND MINERAL SURFACES: PRINCIPLES AND APPLICATIONS - Bedzyk M.J.; Cheng L. (My University, 2002)
With a penetration depth ranging from microns to millimeters, Ångstrom-wavelength X-rays are an ideal probe for studying atomic-scale buried structures found in the natural environment, such as impurities in minerals and adsorbed ions at mineral-water interfaces. But this penetration depth also makes an X-ray beam inherently less useful as a spatially localized probe. Using the superposition of two coherently coupled...